Antibiotic Susceptibility Pattern of Bacterial Isolates Causing Wound Infection Among the Patients Visiting B & B Hospital - Yakha, Jaya Krishna; Sharma, Amit Raj; Dahal, Nawaraj; Lekhak, Binod; Banjara, Megha Raj (Nepal Journal of Science and Technology, 2015)
A wound is any physical injury involving a break in the skin, and exposed subcutaneous tissues provide a favorable substratum for a wide variety of microorganisms to contaminate and colonize. In this study a total of 870 plus samples were collected from patients visiting B & B hospital suspecting wound infection and then analyzed. The causative agents were isolated, identified by culture and biochemical tests and their susceptibility pattern to antibiotics were determined by using CLSI guidelines. Out of total samples, 476(44.8%) showed bacterial growth. Among growth cases 22.9% were mixed growths. Among all bacterial isolates, 12 species were identified of them, 70.6% were Gram-negative and 29.4% were Gram-positive. Among Gram-positive isolates, Staphylococcus. Aureus (74.2%) was most common followed by CoNS (8.6%), Non hemolytic Streptococci (8.6%), Enterococcus spp. (4.3%) and â -haemolytic Streptococci (4.3%). Among Gram-negative bacteria, the most common isolate was Pseudomonas aeruginosa (31.5%) followed by E.coli (24.8%), Acinetobacter spp. (14.6%), Enterobacter spp. (14.0%) and Klebsiella spp. (13.4%). Proteus spp. and Citrobacter spp. were less common. With regard to AST pattern, S. aureus was most susceptible to chloramphenicol and highly resistance to penicillin. Among them, 7.7% were MRSA. For other Gram-positive isolates as well, effective drug was found to be chloramphenicol. For P. aeruginosa, the most effective drug was imipenem (94.3%) followed by amikacin (63.2%). Likewise, for other Gram-negative bacteria most effective drug was imipenem followed by amikacin. Among the total P. aeruginosa isolates, 58.5% were found to be MDR. For all these P. aeruginosa isolates MIC on gentamycin and ciprofloxacin illustrate the simultaneous presence of ciprofloxacin resistance and reduced gentamycin susceptibility. These results indicated that antibiotic resistance in Gram-positive and Gram-negative bacteria were increasing in alarming trend that leads to the failure of treatment. DOI: http://dx.doi.org/njst.v15i2.12121 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 91-96